Serum paraoxonase-1 as a marker of oxidative stress and pulmonary dysfunction in sarcoidosis: association with disease activity and prognostic potential - Bozkürk, Mine Büşra; Günay, Ersin; Ogan, Nalan; Candemir, İpek; Eker, Uğurcan; Öztürk, Alpaslan (Frontiers in Immunology, 2026)
ObjectivesSarcoidosis is a multisystem granulomatous disorder characterized by an oxidative imbalance and inflammatory activation. Paraoxonase-1 (PON1) is a high-density lipoprotein–associated antioxidant enzyme that plays a protective role against oxidative stress. This study aimed to evaluate the serum PON1 activity in patients with sarcoidosis, its relationship with disease stage, and its association with pulmonary function and routine biochemical parameters.Materials and methodsA total of 45 patients with sarcoidosis and 45 age- and sex-matched healthy controls were included. Complete blood counts, biochemical parameters, and pulmonary function test results were evaluated. Serum PON1 activity was colorimetrically determined using a commercial kit. Statistical analyses included correlation, logistic regression, receiver operating characteristic (ROC) curves, and partial least squares discriminant analysis (PLS-DA).ResultsSerum PON1 activity was significantly lower in patients with sarcoidosis than in the healthy controls (p<0.001). PON1 levels showed strong positive correlations with FEV1 (r=0.835), FVC (r=0.807), and DLCO (r=0.905), indicating that decreased antioxidant capacity parallels impaired pulmonary function. ROC analysis demonstrated that PON1 effectively differentiated patients from controls (AUC = 0.838; sensitivity, 75%; specificity, 82% at ≤210.53 U/L). PON1 levels declined progressively with increasing disease stages (p<0.05). Logistic regression analysis revealed that higher BMI and reduced FEV1 were independent predictors of sarcoidosis, whereas PON1 lost significance after adjusting for covariates.ConclusionSerum paraoxonase activity is markedly reduced in sarcoidosis and is correlated with disease severity and pulmonary dysfunction, suggesting increased oxidative stress. Although not an independent predictor, PON1 may serve as a useful adjunctive biomarker, particularly for evaluating disease severity in Stage II and advanced stages, rather than for early diagnosis.